The mediation role of moral judgments on the relationship between digital leadership and organizational wisdom - Atti, liqaa Mutter; Salih, Roaa Mahdi Mohammed; Mohammad, Suleiman Ibrahim Shelash; Vasudevan, Asokan; Hunitie, Mohammad Faleh Ahmmad (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to examine the relationship between digital leadership and organizational wisdom, with the mediating role of ethical judgments. To this end, 30 managers and employees from the General Company for Petrochemical Industries in Basra were randomly selected as the sample. The research variables were assessed using the questionnaires of "Digital Leadership by AlNuaimi et al. [1], Organizational Wisdom by Brown and Green, and Ethical Judgments by Gregory." The data obtained were analyzed using a quantitative approach, and Smart PLS version 3 software was utilized for data analysis. The results indicated that digital leadership and organizational wisdom are interdependent and recognized as influential factors in the success of organizations in today's world. The interaction between these two concepts can assist in achieving strategic goals and ensuring sustainable success in dynamic markets. Furthermore, ethical judgments can play a significant role in shaping the relationship between digital leadership and organizational wisdom. Ethical leadership, adhering to moral principles, can enhance organizational wisdom more effectively by promoting trust, knowledge sharing, and accountability.